A process-sociology analysis of religious practices and Japanese martial arts - Raúl Sánchez García (Universidad de León, 2023)
This paper uses primary and secondary sources to provide a process-sociological analysis of the relationship between religious practices and Japanese martial arts. It problematises the taken for granted role of Zen Buddhism as the sole influence on the development of Japanese martial arts. Such essential connection is inaccurate and anachronistic. Religious and martial practices developed as part of processes of sociogenesis (state formation) and psychogenesis (habitus) during three different key stages: (1) Medieval Japan (1185-1600): during this stage, warriors (bushi) progressively became the predominant rulers across the country, enforcing law by sheer force. Warriors seasoned in combat used esoteric practices (spells, magic rituals) as part of their psychological arsenal for warfare, as practical means of action. The cult of the Buddhist deity Marishiten held special interest for the bushi originating martial traditions (ryu). (2) Tokugawa shogunate (1600-1848): the pacification of the country by the central military court implied a more detached approach to martial arts by samurai. Within this milieu, the samurai acted as a retainer/bureaucrat whose main mission was to keep order in a stratified society and to serve his lord, something that Zen practices helped to incorporate in the samurai ethos. (3) Early Showa period (1926-1945): this stage featured a progressive militarisation of people and the instigation of a strong involvement towards the Japanese nation, considered as the main (symbolic) survival unit. Budo (martial arts) was connected to shinto (functioning as a 'state religion') and embodied the imperial bushido message. Zen provided a legitimation of violence for citizen-soldiers with a personality structure that presented self-doubts on killing someone and fear of being killed.